Generalized riemann-stieltjes operators between hardy spaces and weighted bergman spaces - Xiangling, Zhu (Utilitas Mathematica, 2013)
Let m be a nonnegative integer and g ε H(B) such that g(0) = 0. We define a new integral-type operator, called the generalized Riemann-Stieltjes operator, as follows: Lg(m) f(z) = ∫01 Rmf(tz)g(tz)dt/t, z ε B. The boundedness of the generalized Riemann-Stieltjes operator between Hardy spaces and weighted Bergman spaces in the unit ball are investigated in this paper.